LITERATURE STUDY: THE RELATIONSHIP BETWEEN FEEDING PRACTICES, HEALTHCARE AND CHILD HYGIENE WITH THE IMPACT OF STUNTING IN 1-2-YEAR-OLD CHILDREN - Sahar, Yarzuk; Tosepu, Ramadan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
The term "stunting" refers to the long-term prevalence of malnutrition in toddlers and the effects it has on both physical and cognitive development. The goal of this study was to examine several publications about feeding habits, child health, and cleanliness about stunting in children between the ages of one and two years. This study approach employs a descriptive method using a literature Methodology of study with various references, such as research articles or journals, annual journal reviews, reports, and various other sources. The results of the article analysis were then developed into a review of the review literature. The conclusion in this research literature is that the incidence of stunting in children between the ages of one and two years is correlated with feeding practices, health care, and child hygiene. Keywords: health care methods, hygiene, feeding practices, stunting